Southern Outcast : Hinton Rowan Helper and The Impending Crisis of the South - Brown, David, 1968 April 25- (Book collections on Project MUSE., 2006)
Hinton Rowan Helper (1829-1909) gained notoriety in nineteenth-century America as the author of The Impending Crisis of the South (1857), an antislavery polemic that provoked national public controversy and increased sectional tensions. In his intellectual and cultural biography of Helper-the first to appear in more than forty years-David Brown provides a fresh and nuanced portrait of this self-styled reformer, exploring anew Helper's motivation for writing his inflammatory book. Brown places Helper in a perspective that shows how the society in which he lived influenced his thinking, beginning.